2020
DOI: 10.1186/s13054-020-03276-9
|View full text |Cite
|
Sign up to set email alerts
|

ICU admission body composition: skeletal muscle, bone, and fat effects on mortality and disability at hospital discharge—a prospective, cohort study

Abstract: Background Reduced body weight at the time of intensive care unit (ICU) admission is associated with worse survival, and a paradoxical benefit of obesity has been suggested in critical illness. However, no research has addressed the survival effects of disaggregated body constituents of dry weight such as skeletal muscle, fat, and bone density. Methods Single-center, prospective observational cohort study of medical ICU (MICU) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 43 publications
(49 reference statements)
1
30
1
Order By: Relevance
“…The main finding of our study was that malnutrition as assessed with SGA, and risk of malnutrition as assessed with the NRS-several other works, we showed that ICU patients with malnutrition have the worst outcome (11,12). Also, sarcopenic patients have the worst outcome in the ICU (13)(14)(15)(16)(17)(18)(19). But this work is the first one assessing nutritional risk and malnutrition in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 49%
“…The main finding of our study was that malnutrition as assessed with SGA, and risk of malnutrition as assessed with the NRS-several other works, we showed that ICU patients with malnutrition have the worst outcome (11,12). Also, sarcopenic patients have the worst outcome in the ICU (13)(14)(15)(16)(17)(18)(19). But this work is the first one assessing nutritional risk and malnutrition in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 49%
“…First, this was a single-center observational study, and the design precluded the determination of a causal association between sarcopenia in the ICU and 1-year mortality. Second, the study population was smaller than that in previous studies [ 6 , 10 , 11 ]. Based on the results obtained, we believe it is necessary to replicate the study on larger sample sizes in the future.…”
Section: Discussionmentioning
confidence: 89%
“…Skeletal muscle wasting and the development of intensive care unit-acquired weakness (ICU-AW) dramatically affect mortality and mobility disability after ICU discharge [ 1 , 2 , 3 ]. Moreover, skeletal muscle mass at ICU admission has been associated with mortality [ 4 , 5 , 6 ]. Thus, the value of assessing skeletal muscle mass and function in ICU patients has been emphasized in recent years [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle is important to surviving critical illnesses [ 1 ]. At the intensive care unit (ICU) admission, higher muscle mass is associated with decreased mortality [ 2 ]. After the ICU admission, progressive muscle atrophy occurs, and the atrophy is associated with ICU acquired weakness and mortality [ 3 ].…”
Section: Introductionmentioning
confidence: 99%